Successful treatment of multifocal cutaneous leishmaniasis with miltefosine - Bhushan Madke; Vidya Kharkar; Siddhi Chikhalkar; Sunanda Mahajan; Uday Khopkar (Wolters Kluwer Medknow Publications, 2011)
We report a 48-year-old immunocompetent male, resident of Central India, who presented with slowly progressive asymptomatic multiple red lesions on different parts of body. On enquiry, the patient gave history of travel to Middle East 6 months back. Examination showed 10 crusted erythematous indurated plaques and nodules over forearms, left leg, right index finger, left wrist and dorsa of both feet. Histopathological examination of tissue biopsy showed multiple intracellular as well as extracellular leishmania donovan bodies. Keeping in mind the higher rate of side effects to pentavalent antimony, we treated this patient with oral miltefosine 50 mg bid and the lesions showed complete resolution over 4 months of therapy.